The Santiago Consensus : From Vision to Reality - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed a new consensus on economic and social policy in this hemisphere that has been taking shape. This new consensus is one based on recognition of the paramount importance of what I called a few months ago in Hong Kong "The Challenge of Inclusion" — the challenge of ensuring that economic progress can become a reality in the lives of all the people of this region, especially the tens of millions who until now been very largely left behind. Chile has made commitments to a new model of Open Regionalism. The consensus goes beyond economics and finance, into the social dimension of development. It is time to retire once and for all that tired old phrase of the so-called Washington Consensus. In addition to financial resources, the Bank is determined to harness the incredible power of new information technologies, and a new spirit of openness and partnership, to make knowledge of global best-practice in development accessible to all. We are already engaged in building the internal architecture of a "Knowledge Bank." The Bank of the future will be committed to pulling its weight in translating the Santiago Consensus into reality at both the national and the regional level.